Hubungan Anemia dan Prestasi Belajar Pada Remaja Putri - Nurul Arifin, Astri Siska; Handayani, Ririn; Handayani, Yuni (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2024)
Anemia, a prevalent health condition among adolescents, can significantly impair cognitive function and academic performance. Iron deficiency, a primary cause of anemia in young females, arises from insufficient intake of iron, vitamin B12, and folic acid, essential for erythropoiesis. The reduction in hemoglobin levels associated with iron deficiency leads to diminished oxygen delivery to tissues, compromising cellular metabolism and cognitive development. Consequently, individuals with anemia may exhibit decreased work productivity and difficulty concentrating. This study aimed to investigate the correlation between anemia and academic achievement among female students at Baitul Hikmah Tempurejo Vocational School. A cross-sectional correlational design was employed, with a population of 43 Class XII female students. Simple random sampling was used to select 39 participants using the Slovin formula. Data analysis was conducted using the chi-square test. Findings revealed that 61.5% of the female students were anemic, while 38.5% were not. Additionally, 66.7% of the students failed to meet academic standards, compared to 33.3% who passed. Statistical analysis using the chi-square test indicated a weak correlation between anemia and learning achievement (p = 0.005). The study suggests a minimal association between anemia and academic performance among female students at Baitul Hikmah Tempurejo Vocational School. It is recommended that these students enhance their understanding of the potential impact of anemia on their studies.